1991
DOI: 10.1161/01.res.68.6.1560
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy of the aging human heart. Myocyte loss and reactive cellular hypertrophy.

Abstract: To determine the effects of aging on the human myocardium, 67 O ne of the major difficulties encountered in the study of the effects of age on the cardiovascular system is the differentiation of the aging process itself from the presence of specific disease states. Atherosclerosis, diabetes, and ischemic heart disease are common events in humans, and the severity of these pathological conditions increases with age. Because the contribution of these variables to the alterations of the aged myocardium cannot e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
333
2
21

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(376 citation statements)
references
References 33 publications
20
333
2
21
Order By: Relevance
“…Some collagen family members were also up-regulated, including Type XV collagen alpha 1, Type VI collagen alpha 3, Type IV collagen alpha 1, and Type VI collagen alpha 2. These observations are consistent with previous findings that the aging heart undergoes ECM protein deposition (30), fibrosis (31), and cardiomyocyte hypertrophy (11).…”
Section: Aging Results In Expression Of Genes Encoding Structural Prosupporting
confidence: 93%
See 1 more Smart Citation
“…Some collagen family members were also up-regulated, including Type XV collagen alpha 1, Type VI collagen alpha 3, Type IV collagen alpha 1, and Type VI collagen alpha 2. These observations are consistent with previous findings that the aging heart undergoes ECM protein deposition (30), fibrosis (31), and cardiomyocyte hypertrophy (11).…”
Section: Aging Results In Expression Of Genes Encoding Structural Prosupporting
confidence: 93%
“…Age-related changes in human and rodent hearts include a reduction in the number of myocytes (10,11), myocyte hypertrophy (11,12), cardiac fibrosis (13), lipofuscin pigment accumulation (14), a reduction in calcium transport across sarcoplasmic reticulum membrane (15), and alterations in the response to ␤-adrenergic stimulation (16). Collectively, these alterations likely contribute to age-related heart diseases being the leading cause of mortality in the U.S. (17).…”
mentioning
confidence: 99%
“…Both phenomena decrease the reserve of the myocardium to sustain increases in mechanical load generated by myocardial infarction, systemic hypertension, or their combination. Diabetic cardiomyopathy resembles the aged heart in men, in which tissue damage is not apparent in spite of an agedependent loss of myocytes and reactive hypertrophy of the viable cells (Olivetti et al, 1991(Olivetti et al, , 1995. Similar findings have been obtained in aging Sprague-Dawley rats (Anversa et al, 1986).…”
Section: Figuresupporting
confidence: 78%
“…20 Standard published human ECG results consist of an HR of 60-100 beats/min, a mean PR interval of 120-200 ms, a mean QRS interval of <120 ms, and a mean QT interval of 420 ms. 21,22 In an earlier National Health Statistics Report, the mean weight of female adults over 20 years of age in the United States from 2003 to 2006 was 74.7 kg and that of males was 88.3 kg. 23 Additionally, a study evaluating the diseasefree aging heart reported BW from adults over 20 years of age ranging from 51 to 99 kg and HW of 123 to 306 g. 24 …”
Section: Sinclairmentioning
confidence: 99%